Impact of the Endocannabinoid System on Bone Formation and Remodeling in p62 KO Mice - Keller, Christina; Yorgan, Timur Alexander; Rading, Sebastian; Schinke, Thorsten; Karsak, Meliha (Frontiers in Pharmacology, 2022)
Several studies have shown that the G-protein coupled cannabinoid receptor CB2 and its interaction partner p62 are molecularly involved in bone remodeling processes. Pharmacological activation of the CB2 receptor enhanced bone volume in postmenopausal osteoporosis and arthritis models in rodents, whereas knockout or mutation of the p62 protein in aged mice lead to Paget's disease of bone-like conditions. Studies of pharmacological CB2 agonist effects on bone metabolism in p62 KO mice have not been performed to date. Here, we assessed the effect of the CB2-specific agonist JWH133 after a short-term (5 days in 3-month-old mice) or long-term (4 weeks in 6-month-old mice) treatment on structural, dynamic and cellular bone morphometry obtained by µCT of the femur and histomorphometry of the vertebral bodies in p62 KO mice and their WT littermates in vivo. A genotype-independent stimulatory effect of CB2 on bone formation, trabecular number, and trabecular thickness after short-term treatment and on tissue mineral density after long-term treatment was detected, indicating a weak osteoanabolic function of this CB2 agonist. Moreover, after short-term systemic CB2 receptor activation, we found significant differences at the cellular level in the number of osteoblasts and osteoclasts only in p62 KO mice, together with a weak increase in trabecular number and a decrease in trabecular separation. Long-term treatment showed an opposite JWH133 effect on osteoclasts in WT versus p62 KO animals and decreased cortical thickness only in treated p62 KO mice. Our results provide new insights into CB2 receptor signaling in vivo and suggest that CB2 agonist activity may be regulated by the presence of its macro-molecular binding partner p62.